2014
DOI: 10.1108/dpm-05-2013-0086
|View full text |Cite
|
Sign up to set email alerts
|

Issues raised by nurses and midwives in a post-disaster Bantul community

Abstract: Purpose -Bantul in Central Java was the most severely damaged area by a devastating earthquake in May 2006. Even after being victims themselves, nurses and midwives at public health centers worked devotedly. The purpose of this paper is to identify the nurses' and midwives' perceptions and understanding of their roles, as well as the needs of training in disaster preparedness and management. Design/methodology/approach -Focus group discussions and questionnaire survey were conducted with 11 nurses and 11 midwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 49 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…Six of the seven papers reporting on the response phase of an emergency [43, 4851] and a paper which detailed the response and recovery phases [49] discussed the role of midwives in providing maternal and newborn health services. Midwives were reported as being involved in births at both health facilities and in women’s homes [42, 46, 48, 50, 51]. Birthing at home was often supported by midwifery staff when access to facilities was compromised by ongoing conflict [42, 49, 50].…”
Section: Resultsmentioning
confidence: 99%
“…Six of the seven papers reporting on the response phase of an emergency [43, 4851] and a paper which detailed the response and recovery phases [49] discussed the role of midwives in providing maternal and newborn health services. Midwives were reported as being involved in births at both health facilities and in women’s homes [42, 46, 48, 50, 51]. Birthing at home was often supported by midwifery staff when access to facilities was compromised by ongoing conflict [42, 49, 50].…”
Section: Resultsmentioning
confidence: 99%
“…As observed, one common vulnerability identified was the lack of disaster management training for staff 34,47,53,66,78,115 . Our review also highlighted a lack of disaster exercise or testing of plans.…”
Section: Importance Of Developing System Capacity and Capabilitiesmentioning
confidence: 98%
“…In addition it was also reported that staff may themselves be emotionally affected by their own personal earthquake experiences 75,115 and feel ill prepared to respond to patient needs 53 . Indeed, some healthcare staff were reported to have poor mental health outcomes afterwards 76,122 , particularly those working in public sector healthcare settings 121 .…”
Section: Coordination Response and Logisticsmentioning
confidence: 99%
See 2 more Smart Citations